INFLUENCE OF MACHINING TECHNOLOGIES ON VALUES OF RESIDUAL STRESSES OF OXIDE CUTTING CERAMICS - Jakub Němeček; Kamil Kolařík; Jiří Čapek; Nikolaj Ganev (Acta Polytechnica CTU Proceedings)
Currently, the intensive development of engineering ceramic and effort to replace sintered carbides as cutting materials are in progress. With the development of the sintering technology it is now possible to produce compact ceramic cutting samples with very good mechanical properties. The advantage of these materials is their easy accessibility and low purchase price. In this work, the influence of the finishing machine technology on the values of surface residual stresses of cutting ceramic samples Al2O3+TiC were studying. The samples were supplied by Moscow State University of Technology STANKIN. Measurements made in the X-ray diffraction laboratory at the Department of solid state engineering were performed for both the phases. The influence of the parameters of machining to residual stresses was studied and the resulting values were compared with each other.